1998
DOI: 10.1007/s004320050215
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for hepatocellular carcinoma in 967 patients with cirrhosis

Abstract: The annual incidence of hepatocellular carcinoma was 2.1%. These results, although confirming that age is a risk factor for hepatocellular carcinoma in cirrhosis, indicate that alcohol abuse, male sex, and concurrent hepatitis B and C virus infection do not involve a higher risk of developing liver cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Only two of them (Benvegnu`et al, 1994;Chiaramonte et al, 1998) showed an additive synergism between the two infections, while the others (Zoli et al, 1996;Del Olmo et al, 1998;Benvegnu`et al, 2004;Sangiovanni et al, 2004) showed independence between the two infections in causing HCC.…”
Section: Overt Hepatitis B Virus Infectionmentioning
confidence: 96%
“…Only two of them (Benvegnu`et al, 1994;Chiaramonte et al, 1998) showed an additive synergism between the two infections, while the others (Zoli et al, 1996;Del Olmo et al, 1998;Benvegnu`et al, 2004;Sangiovanni et al, 2004) showed independence between the two infections in causing HCC.…”
Section: Overt Hepatitis B Virus Infectionmentioning
confidence: 96%
“…5,6,8,22,36,64,68,98,[331][332][333] Thirteen studies were excluded. 5,6,8,10,68,284,287,289,293,298,333 Details of the studies are shown in Table 17.…”
Section: Selection Of Parameters: Baseline Characteristics Age At Diamentioning
confidence: 99%
“…in the middle of this range). As there is no reason to suspect that gender imparts a differential risk of mortality in alcohol-related cirrhosis, this figure was used as the base-case point estimate, and the proportion was varied between 50% (an arbitrary value to explore evidence that ALD is becoming more widespread among females 334 ) and 90.2% (as per del Olmo and colleagues' findings 332 ) in sensitivity analyses.…”
Section: Alcoholic Cirrhosismentioning
confidence: 99%
See 1 more Smart Citation
“…3,14 Predisposing factors associated with HCC, such as viral hepatitis infection, alcohol abuse, metabolic disorders, and other environmental agents, also induce cirrhosis. 15,16 However, it is not clear whether these factors induce HCC directly or whether they act indirectly by producing chronic liver injury and regeneration. Epidemiologic data indicate that patients with chronic hepatitis B (HBV) or C virus (HCV) infection seem to be at an extremely high risk for developing HCC.…”
mentioning
confidence: 99%